Radioimmunoassay of bleomycin in plasma and urine. - Teale, J. D. (1977)
Antibodies to bleomycin were raised by immunization of sheep and rabbits with bleomycin-albumin conjugates. The combination of a high-titre, high-avidity sheep antiserum and iodinated bleomycin produced a radioimmunoassay sensitive to 8 ng of bleomycin per ml of plasma or urine. Untreated specimens (100 microliter) of plasma or urine could be added directly to the assay tubes. The antiseerum was specific for bleomycin and showed no cross-reaction with other anticancer agents used in combination chemotherapy. Over a concentration range of 20-100 ng/ml, recovery of bleomycin from plasma was 110% and from urine, 93%. Repeated assay of plasma samples showed a decrease in bleomycin levels unless the samples were kept at 4 degrees C or below.Assay of bleomycin levels in plasma and urine from patients under treatment with bleomycin showed similarities with results reported using a microbiological assay. The radioimmunoassay offers a more reliable, rapid and sensitive method for the measurement of bleomycin.